2003
DOI: 10.1029/2002jd003001
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends of inorganic chlorine from ground‐based infrared solar spectra: Past increases and evidence for stabilization

Abstract: [1] Long-term time series of hydrogen chloride (HCl) and chlorine nitrate (ClONO 2 ) total column abundances has been retrieved from high spectral resolution ground-based solar absorption spectra recorded with infrared Fourier transform spectrometers at nine NDSC (Network for the Detection of Stratospheric Change) sites in both Northern and Southern Hemispheres. The data sets span up to 24 years and most extend until the end of 2001. The time series of Cl y (defined here as the sum of the HCl and ClONO 2 colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 85 publications
(130 reference statements)
10
76
0
Order By: Relevance
“…For example, extended NDACC FTIR data sets, combined with HALOE observations from UARS gave evidence for a stabilization of stratospheric chlorine around the mid-1990s (Rinsland et al, 2003). Subsequently, NDACC showed there to be a decrease in atmospheric HCl and ClONO 2 at rates ~ 1%/year in both hemispheres, between 80°N and 78°S (Kohlhepp, et al, 2012).…”
Section: Providing Precise Documentation Of the Multi-decadal Trends mentioning
confidence: 99%
“…For example, extended NDACC FTIR data sets, combined with HALOE observations from UARS gave evidence for a stabilization of stratospheric chlorine around the mid-1990s (Rinsland et al, 2003). Subsequently, NDACC showed there to be a decrease in atmospheric HCl and ClONO 2 at rates ~ 1%/year in both hemispheres, between 80°N and 78°S (Kohlhepp, et al, 2012).…”
Section: Providing Precise Documentation Of the Multi-decadal Trends mentioning
confidence: 99%
“…Recently, chlorine levels seem to have begun decreasing in the stratosphere (WMO, 2003;Rinsland et al, 2003). It is now being discussed whether ozone also might show signs of a beginning recovery (Newchurch et al, 2003;Steinbrecht et al, 2004;Reinsel et al, 2005).…”
Section: Linear Trendmentioning
confidence: 99%
“…However, due to the 1987 Montreal protocol agreement (and the subsequent adjustments), ozone depleting substance (ODS) emissions have slowly been phased out. It has been estimated that the total inorganic loading of tropospheric Cl peaked in 1993 (Rinsland et al, 2003) and has decreased by ∼5 % through early 2002 (O' Doherty et al, 2004). As it is estimated that it takes 3-6 years for air to be transported into the middle and upper stratosphere (Stiller et al, 2008), then peak stratospheric values are suggested to be somewhere between and 1999(WMO, 2006.…”
Section: Introductionmentioning
confidence: 99%